Efficient online handwritten chinese character recognition system using a two-dimensional functional relationship model - Chang, Yun Fah; Lee, Jia Chii; Mohd Rijal, Omar; Syed Abu Bakar, Syed Abdul Rahman (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents novel feature extraction and classification methods for online handwritten Chinese character recognition (HCCR). The X-graph and Y -graph transformation is proposed for deriving a feature, which shows useful properties such as invariance to different writing styles. Central to the proposed method is the idea of capturing the geometrical and topological information from the trajectory of the handwritten character using the X-graph and the Y-graph.
Keywords: 2D functional classifier; coefficient of determination; handwritten Chinese character recognition; Haar wavelet; multidimensional functional relationship model